Decorating MnO2 nanosheets on MOF-derived Co3O4 as a battery-type electrode for hybrid supercapacitors. Issue 44 (11th October 2022) - Babu, S. Kishore; Gunasekaran, B.; Sridharan, M.; Vijayakumar, T.
Abstract : Metal–organic framework-derived materials are now considered potential next-generation electrode materials for supercapacitors. Abstract : Metal–organic framework-derived materials are now considered potential next-generation electrode materials for supercapacitors. In this present investigation, Co3 O4 @MnO2 nanosheets are synthesized using ZIF-67, which is used as a sacrificial template through a facile hydrothermal method. The unique vertically grown nanosheets provide an effective pathway for rapidly transporting electrons and ions. As a result, the ZIF-67 derived Co3 O4 @MnO2 -3 electrode material shows a high specific capacitance of 768 C g −1 at 1 A g −1 current density with outstanding cycling stability (86% retention after 5000 cycles) and the porous structure of the material has a good BET surface area of 160.8 m 2 g −1 . As a hybrid supercapacitor, Co3 O4 @MnO2 -3//activated carbon exhibits a high specific capacitance (82.9 C g −1 ) and long cycle life (85.5% retention after 5000 cycles). Moreover, a high energy density of 60.17 W h kg −1 and power density of 2674.37 W kg −1 has been achieved. This attractive performance reveals that Co3 O4 @MnO2 nanosheets could find potential applications as an electrode material for high-performance hybrid supercapacitors.